ANALISIS SIFAT MEKANIK ALAT PENGUPAS KELAPA PRODUKSI INDUSTRI KECIL PANDAI BESI DI MINAHASA - Alexander Rano Sampelobo Pareang; Tritya A R Arungpadang; Romels C A Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
ABSTRACT This research aim to determine the hardness number, the absorb energy and the price of coconut peeler material impact and to analyze the differences of mechanical properties of coconut peeler production from several blacksmith craftsmen in Minahasa. Basic material of coconut peeler is spring steel car. The coconut peeler is the result of three blacksmith craftmen centers in Minahasa. From the test result of the hardness specimen without treatment, the highest hardness value is 711.3774369 HVN while with the specimens of hardness test with treatments which the value for Wulauan is 259.1432198 HVN, for Parepei is 315.2173625 HVN , for Tombasian is 262, 1731511 HVN. As for the impact testing, specimen with treatment Wulauan 19.89 J energy absorption and impact the price of 1,321 J / mm², which is the energy absorption and impact the price of the highest compared with the treatment of test specimens in Parepei who holds 15.94 J energy absorption and impact prices 1,063 J / mm², and in Tombasian which has energy absorption and the price impact of 4.45 j 0.297 J / mm², as well as the untreated specimens that have absorption energy of 6.42 J and impact the price of 0.642 J / mm². . Keywords: Coconut Peeler, Hardness Number, Absorption Energy, Impact Price.